(untitled) (Current Horticulture, 2024)
An experiment was conducted to find out the effects of integrated nutrient management on yield, quality and economics of chilli (Capsicum annuum L.) during 2012 rabi season at Research Farm, JNKVV, College of Agriculture, Tikamgarh, Madhya Pradesh. There were 10 treatment combinations (V1I1. V1I2, V1I3, V1I4, V1I5, V2I1, V2I2, V2I3, V2I4, V2I5) as V1, Pusa Jwala; V2, Garima 12 and INM facors, I1- recommended dose of fertilizer (RDF) or the control (100:50:50 kg NPK/ha), I2- RDF + FYM (10 t/ha), I3 - RDF + vermicompost (2.5 tonnes/ha), I4 - RDF + Vesicular arbuscul mycorrhiza (VAM) @ 2 kg/ha, I5 - RDF + Azospirillum in factorial randomized block design with 3 replications. Application of RDF + vermicompost 2.5 tonnes/ha showed significant increase in fruit yield (271.5 g/plant) and fresh fruit yield of 6816 kg/ha. There was lowest fruit yield and fresh fruit yield of chilli (227.8 g/plant and 4218 kg ha, respectively) with recommended dose of fertilizer (RDF) or the control (100:50:50 kg NPK/ha). Combined application of RDF + vermicompost 2.5 tonnes/ha showed significant increase in ascorbic acid content (190.8 mg/100 g). There was highest net return (181607 Rs/ha), with benefit : cost ratio of 3.19. However, lowest ascorbic acid content (170.8 mg/100 g) and minimum net returns (95194 Rs/ha) were recorded in the control (100:50:50 kg NPK/ha) while there was minimum B:C ratio (3.19) with I2.